Diagnosis of Mineral Deficiencies in Chir (pinus Roxburghii) Seedlings - Kaul, O.N.; Sharma, R.P. (Indian Forester, 1963)
1. Sarvaritermes faveolus Chatterjee and Thakur has been recorded as one of the wood boring termite, attacking Alnus nitida End1. (kosh) in Kulu valley, Punjab. 2. It attacks aged trees, and it also attacks its partially dead parts. 3. It makes a network of large irregular galleries inside the trunk of trees which are filled with dark brown faecal matter cemented together. 4. The castes so far known are, alates, soldiers and workers. 5. The emergence of alates occurs during the monsoon season